Mitochondrial poly(A) polymerase is involved in tRNA repair. Issue 20 (9th September 2015) - Fiedler, Mario; Rossmanith, Walter; Wahle, Elmar; Rammelt, Christiane
Abstract : Transcription of the mitochondrial genome results in polycistronic precursors, which are processed mainly by the release of tRNAs interspersed between rRNAs and mRNAs. In many metazoan mitochondrial genomes some tRNA genes overlap with downstream genes; in the case of human mitochondria the genes for tRNA Tyr and tRNA Cys overlap by one nucleotide. It has previously been shown that processing of the common precursor releases an incomplete tRNA Tyr lacking the 3′-adenosine. The 3′-terminal adenosine has to be added before addition of the CCA end and subsequent aminoacylation. We show that the mitochondrial poly(A) polymerase (mtPAP) is responsible for this A addition. In vitro, a tRNA Tyr lacking the discriminator is a substrate for mtPAP. In vivo, an altered mtPAP protein level affected tRNA Tyr maturation, as shown by sequencing the 3′ ends of mitochondrial tRNAs. Complete repair could be reconstituted in vitro with three enzymes: mtPAP frequently added more than one A to the 3′ end of the truncated tRNA, and either the mitochondrial deadenylase PDE12 or the endonuclease RNase Z trimmed the oligo(A) tail to a single A before CCA addition. An enzyme machinery that evolved primarily for other purposes thus allows to tolerate the frequent evolutionary occurrence of gene overlaps.